Photodegradation of benzisothiazolinone: Identification and biological activity of degradation products. (February 2020) - Varga, Zsuzsanna; Nicol, Edith; Bouchonnet, Stéphane
Abstract: The photodegradation of benzisothiazolinone was studied in water under UV–Vis irradiation and led to fourteen photoproducts. Chemical structures of these compounds were elucidated using GC-MS, LCMS/MS, and FT-ICR-MS experiments. Based on the chemical structures determined and their appearance order, a photo induced-degradation mechanism of benzisothiazolinone has been proposed, which combines isomerization, oxidation, hydroxylation, hydrolysis, and elimination processes. In silico tests on mutagenicity, Fathead minnow LC50 and oral rat LD50 were carried out to estimate the toxicity of the photoproducts. Compared with experimental data, the calculated oral rat LD50 values were found to be the most relevant and thus used for toxicity estimation. The photoproducts including a phenolic or a sulfino group or both functions were found potentially more toxic than benzisothiazolinone. Highlights: The UV-VIS photodegradation of benzisothiazolinone led to fourteen photoproducts. Degradation mechanism has been proposed based on photoproducts' structures. Some photoproducts are potentially more toxic than benzisothiazolinone.